When cluster headache was called histaminic cephalalgia (Horton’s headache) - Fanciullacci, M. (Springer-Verlag, 2006)
The Author revives his experiences and reminiscences in the frontline research and everyday clinical practice dealing with what was then called "histaminic cephalalgia" (Horton’s headache). In this context, the Author, one of the historical representatives of the School of Florence, reports an outline of the contribution of this pioneering period in order to promote research ideas concerning possible brain involvement in cluster headache (CH) pathogenesis, which is currently accepted worldwide. The recent history of CH has registered remarkable progress in revealing the mystery of this pathology and it is likely that, in the near future, through the development of better education and new treatments, the overall suffering of patients will be further minimised.